The association between Thoroughbred racehorse training practices and musculoskeletal injuries in Victoria, Australia - Wong, Adelene S. M.; Morrice-West, Ashleigh V.; Hitchens, Peta L.; Whitton, R. Chris (Frontiers in Veterinary Science, 2023)
Catastrophic musculoskeletal injuries (CMI) in horses are associated with both too little and too much high-speed exercise. In order to advise trainers on training and management strategies that minimize the risk of musculoskeletal injury (MSI), a better understanding of how training practices affect MSI in racehorses is needed. Data from prospective studies relating training data and MSI are complicated by the gradual development of pathology and the effect of this on the ability of horses to train consistently prior to the identification of an injury. To circumvent this, 66 Australian Thoroughbred trainers were surveyed on their intended training practices, including rest, pretraining, and race-fit practices. Associations between intended training practices and catastrophic and non-catastrophic race day MSI outcomes in two-year-old and mature (≥ three-year-old) horses were assessed using multivariable negative binomial regression models. The incidence of two-yearold race day MSI was lower for trainers who preferred shorter times (weeks) to trial, less time in fast work pre-trial (p=0.003), shorter, more frequent rest periods (p<0.01) and higher amounts of fast work at 15.5 -16.7 m/s once race-fit (p=0.001). The incidence of mature horse race day MSI was lower for trainers who preferred longer rest periods (p=0.026) and a high-volume pre-trial training strategy comprising a high volume of slower speed gallop training and longer times to trial compared to fast and light training programs (p=0.004) for their mature horses, in addition to higher amounts of fast work at 15.5 -16.7 m/s for their race-fit two-year-olds (p=0.012). Race day CMI incidence was lower for trainers who preferred lower volumes of fast gallop work for their race-fit mature horses (p<0.05). These results suggest that two-year-old training practices could affect MSI risk later in a horse's career, and that age and stage in training (pre-trial, race-fit) are important considerations when developing training practices to minimize the risk of MSI.